Effect of a simple and adherent home exercise program on the physical function of community dwelling adults sixty years of age and older with pre-sarcopenia or sarcopenia - Fujita, Hiroaki; Ishibashi, Hideaki; Maruya, Kohei; Asakawa, Yasuyoshi; Arai, Tomoyuki; Yamaguchi, Haruyasu (Journal of Physical Therapy Science, 2016)
[Purpose] To evaluate the effect of a home exercise program on physical function in community dwelling elderly with pre-sarcopenia or sarcopenia. [Subjects and Methods] Fifty-two community-dwelling individuals, over 60 years and meeting the diagnostic criteria for pre-sarcopenia or sarcopenia, were randomly assigned to intervention group (n=34) and control group (n=18). The intervention group completed 6-months home exercise programs, combining walking with lower limb resistance exercises. Body mass index, skeletal mass index, body fat percentage, handgrip strength, single-leg standing, walking speed (comfortable and maximal), and knee extension strength were evaluated at baseline and post-intervention. Activity was assessed using the 25-question Geriatric Locomotive Functional Scale (GLFS-25) and quality of life using the Euro QOL questionnaire. [Results] Pre- and post-training assessments were completed by 76.5% and 77.8% of participants in the intervention and control groups, respectively. The intervention improved single-leg standing (60.5 s to 77.2 s) and knee extension strength (1.38 Nm/kg to 1.69 Nm/kg). In the control group, maximum walking speed (2.02 m/s to 1.86 m/s) and GLFS-25 score (2.9 to 5.1) worsened. Change of pre-sarcopenia/sarcopenia status was comparable for the intervention (15.4%) and control (14.3%) groups. [Conclusion] A 6-month home exercise program improved physical function in community-dwelling individuals with pre-sarcopenia or sarcopenia.